Free flap reconstruction of plantar weight‐bearing heel defects: Long‐term functional and patient‐reported outcomes. Issue 6 (8th April 2022) - Sayyed, Adaah A.; Towfighi, Parhom; Deldar, Romina; Attinger, Christopher E.; Evans, Karen K.
Abstract: Purpose: Non‐healing plantar weight‐bearing heel ulcers are a challenging problem to treat. Free tissue transfer (FTT) reconstruction of the heel is an opportunity for limb salvage to preserve gait and ambulation. The aim of this study is to describe surgical and functional outcomes in patients who underwent FTT to treat chronic heel ulcers. Methods: A retrospective review of patients who underwent FTT for plantar heel ulcers from 2011 to 2021 was conducted. Patient demographics, comorbidities, perioperative data, postoperative complications, and long‐term outcomes were recorded. Primary outcomes included flap success, complications, postoperative ambulation, patient‐reported outcome measures and limb salvage, with patients stratified into limb salvage or eventual amputation groups. RESULTS: Forty‐four patients underwent 45 heel reconstructions. Average age and BMI were 57.3 years and 30.1 kg/m 2, respectively. Thirty‐eight patients (86.4%) had calcaneal osteomyelitis, 35 patients (79.5%) had diabetes, and 18 patients (40.9%) had peripheral vascular disease (PVD). Immediate microsurgical success rate was 95.6%. At mean follow‐up of 19.6 ± 20.9 months, overall limb salvage rate was 73.3% ( n = 33). Preoperative albumin levels were higher in limb salvage group compared to the amputation group (3.0 vs. 2.4 g/dl, p = .018). Prior stroke history and hypoalbuminemia were significantly higher in the amputation group compared to limb salvage group ( p = .012 and p = .018, respectively). Risk for eventual amputation was associated with PVD (OR 4.0, p = .053), hypoalbuminemia (OR 4.9, p = .020), and postoperative infection (OR 6.3, p = .013). Of the 12 amputations that occurred, the most common indication for amputation was infection ( n = 8, 66.7%), which most often occurred at the original wound location (62.5%). At most recent follow‐up, 90.7% of patients ( n = 39) were ambulatory. CONCLUSION: FTT is an effective alternative to amputation in patients with chronic heel ulcers. Proper patient selection, preoperative optimization, and postoperative care are imperative to the success of this limb salvage procedure.